CHLORITE/SMECTITE - ALKALI FELDSPAR METASOMATIC XENOLITHS FROM HYBLEAN MIOCENIC DIATREMES (SICILY, ITALY): EVIDENCE FOR EARLY INTERACTION BETWEEN HYDROTHERMAL BRINES AND ULTRAMAFIC/MAFIC ROCKS AT CRUSTAL LEVELS - Scribano, Vittorio; Ioppolo, Salvatore; Censi, Paolo (Ofioliti, 2024)
Upper-Miocene tuff-breccia pipes from the Hyblean area (south-eastern Sicily) bear a number of ultramafic and mafic xenoliths (spinel-peridotites, pyroxenites, gabbroic rocks) whose study has led to conclude that the Meso-Caenozoic carbonatic and volcanic succession stands upon a fossil oceanic core-complex, probably connected with the adjacent Ionian crust. Evidence for hydrothermal metasomatism is common in the Hyblean ultramafic and mafic xenoliths. In some cases, extreme metasomatic transformation and shearing have deleted original mineralogy and textures yielding unusual rocks, hereafter called “metasomatites”. These rocks generally exhibit cataclastic texture, their hydrothermal mineral assemblage consisting of Na-rich alkali feldspar, chlorite/smectite (C/S) and/or smectite/illite (S/I) mixed layers, Fe-Ti oxide/ hydroxide ± sieve-textured aegirine-augite ± titanite ± zircon. In addition, relics of Fo91 olivine, probably related to peridotite protoliths, rarely occur in these rocks. Comparing metasomatite whole chemistry to typical Hyblean oxide-gabbro, overall gain in H2O, alkalis, HFSE, U, Th, HREE and significant loss in Ca and Mg are remarkable. The studied xenoliths probably represent fragments of deep-seated, mafic/ultramafic fault-breccia, recording the effects of longlasting hypersaline hydrous fluids circulation in the Hyblean crustal basement.